1984
DOI: 10.2307/1129840
|View full text |Cite
|
Sign up to set email alerts
|

Follow-Up of a Preschool Epidemiological Sample: Cross-Age Continuities and Predictions of Later Adjustment with Internalizing and Externalizing Dimensions of Behavior

Abstract: The continuity of behavioral adjustment from preschool through elementary school and junior high school years was examined. 541 children aged 9-15 years from a preschool epidemiological study were relocated and behavior checklist data obtained. Analyses focused on the relationship between internalizing and externalizing behavior dimensions from the preschool to follow-up periods. It was found that preschool externalizing symptoms were positively correlated with later externalizing and internalizing symptoms in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(40 citation statements)
references
References 27 publications
4
34
0
1
Order By: Relevance
“…Population-based birth cohort studies have shown that childhood psychiatric problems are developmental precursors for a wide range of negative outcomes indicating risk of marginalization including peer rejection, school failure, psychopathology, substance abuse and criminality [4], and the prognoses are often poor [5-14]. Approximately half of those children whom have been identified as aggressive with externalizing behaviour at preschool age eventually develop persistent problems [15,16] and there seems to be a developmental trajectory of early onset ODD that leads to Conduct Disorder (CD) in a proportion of these children [7]. In children, ODD has also been linked to parental depression [17,18], family dysfunction [18], and impairments in parental work performance [19].…”
Section: Introductionmentioning
confidence: 99%
“…Population-based birth cohort studies have shown that childhood psychiatric problems are developmental precursors for a wide range of negative outcomes indicating risk of marginalization including peer rejection, school failure, psychopathology, substance abuse and criminality [4], and the prognoses are often poor [5-14]. Approximately half of those children whom have been identified as aggressive with externalizing behaviour at preschool age eventually develop persistent problems [15,16] and there seems to be a developmental trajectory of early onset ODD that leads to Conduct Disorder (CD) in a proportion of these children [7]. In children, ODD has also been linked to parental depression [17,18], family dysfunction [18], and impairments in parental work performance [19].…”
Section: Introductionmentioning
confidence: 99%
“…Future studies should examine possible mechanisms to provide a deeper understanding of the effects of paternal depression on children. Finally, this sample only included children with significant behavior problems; while this is a very important group, as they are at heightened risk for developing internalizing symptoms (e.g., Fischer et al, 1984; Lavigne et al, 1998), results may differ infamilies where children do not exhibit behavioral difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…Preschoolers with externalizing problems have been found to have higher levels of concurrent internalizing symptoms (Burlaka, Bermann, & Graham-Bermann, 2015; Gilliom & Shaw, 2004) and developmore internalizing symptoms later on (Fischer, Rolf, Hasazi, & Cummings, 1984; Gilliom & Shaw, 2004; Lavigne et al, 1998). In addition, children’s dysthymic symptoms have been found to last longer (by nearly 2 Âœ years) when they experience comorbid externalizing problems (Kovacs, Obrosky, Gatsonis, & Richards, 1997).…”
Section: Depression and Child Behavior Problemsmentioning
confidence: 99%
“…The value of early detection and identiÂźcation of problems and consequent intervention with young children and their families has been recognised for many years. Studies suggest that children with early externalising problems are more likely than comparison children without such early symptoms to have difÂźculties in behavioural control in early school years to middle childhood (Richman, Stevenson, & Graham, 1982;Fisher et al, 1984;Campbell & Ewing, 1990). In line with these studies, intervention in the pre-school years can be seen as a primary preventative strategy (Goldstein, 1977;Blair, 1992).…”
Section: Introductionmentioning
confidence: 99%